Evaluation of the Effects of Various Levels of Maxillary Incisor Protrusion on Upper Lip - Murat Tunca; Yasemin Tunca (Van Tıp Dergisi, 2023)
INTRODUCTION: This study aimed to evaluate the effect of upper central incisors on the upper lip after fixed orthodontic treatment. METHODS: In this retrospective study, 30 individuals aged between 202 and 278 months whose lateral cephalometric radiographs were evaluated at the beginning and end of treatment were included. The study was divided into two groups: Group A, in which the upper incisors protruded by 0–1 mm, and Group B, in which they protruded by 1–3 mm. The soft tissue nasolabial angle, upper lip thickness, and upper lip protrusion values were compared at the beginning and end of treatment in both groups. A Mann-Whitney U test was used to determine the relationship between continuous variables, and Spearman correlation coefficient was used to determine the relationship between these variables. RESULTS: The mean upper incisor protrusion was 0.49 +- 0.3 mm for Group A and 2.29 +- 0.56 mm for Group B. The nasolabial angle was -0.57 +- 1.13° in Group A and -3.78 +- 76° in Group B. The lip thickness was 0.18 +- 0.14 mm in Group A and -0.73 +- 0.49 mm in Group B. The upper lip protrusion was 0.34 +- 0.45 mm for Group A and 1.48 +- 0.45 mm for Group B. There was a statistically significant difference between the groups for all three values (p = 0.001). DISCUSSION AND CONCLUSION: Upper incisor protrusion was used to determine a decrease in nasolabial angle and a decrease in upper lip protrusion. However, when the protrusion amount increased, a decrease in lip thickness was observed.